The Influence of Parenting Patterns, Diarrhea Diseases and Infections on the Incidence of Stunting Toddlers in Poor Families in Medan City - Khadijah Khadijah; Etty Sudaryati; Zulhaida Lubis (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Stunting is a long-term reflection of inadequate food quality and quantity and frequent childhood infections, especially in low economic conditions or poor families. This study aims to analyze the effect of parenting patterns on breastfeeding and complementary feeding, food preparation, environmental hygiene and sanitation practices, caring for children when sick, infectious diseases of diarrhea and Acute Respiratory Infection on the incidence of stunting in toddlers in poor families in Medan City. This research method used a case-control approach. This study was conducted in the Medan City area from November 2022 to December 2023. The study sample population was 364. The study sample was 105 children from poor families by comparing the number of samples in the case group and control samples, namely 35 samples in the case group and 70 in the control group. The sampling technique was carried out using the cluster sampling method. Data were collected using a questionnaire in the form of an interview. The incidence of stunting in children was obtained from the measurement of children's height using a toddler height meter. Data collection used primary data through questionnaires and secondary data through Child Identity Card book data. Data analysis with descriptive univariate analysis, bivariate analysis with chi-square test and multivariate analysis with logistic regression. data processing using SPSS software version 16.0. The results showed that there was a significant influence between breastfeeding and complementary feeding (p-value 0.006) and environmental sanitation hygiene practices (p-value = 0.017) on the incidence of stunting in toddlers from poor families. The dominant factor influencing the incidence of stunting in Medan City is the factor of breastfeeding and complementary feeding that is not good has a risk of 3.473 times experiencing stunting compared to children with good breastfeeding and complementary feeding. Keywords: Parenting, Poor Family, Stunting, Toddler